Metal-Free Synthesis 6-Benzylphenanthridines via Radical Addition/Cyclization of 2-Isocyanobiphenyls - Lu, Yuling; Chen, Li; Chen, Xia; Yao, Meng; Luo, Zengwei; Zhang, Yonghui (Synthesis, 2020)
A simple and practical approach has been established for the synthesis of 6-benzylphenanthridines from benzylic hydrocarbons and 2-isocyanobiphenyls via C(sp3)–H/C(sp2)–H bond functionalization under metal-free condition. The reaction exhibits good functional group tolerance and delivers the target products in moderate to excellent yields. The preliminary mechanistic investigation revealed that a radical intermediate might be involved in this reaction.
Keywords: phenanthridine; metal-free; radical; isocyanobiphenyl; toluene